The Influence of Life Expectancy and Health on Poverty Levels Using Education as an Intervening Approach to Variable Path Analysis - Dhea Nita Rambe; Aini Rahma; Sukardi Sukardi; Ahmad Albar Tanjung (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
In Sibolga City there are several problems that must be resolved, such as high levels of poverty and low levels of life expectancy, health and education. This research aims to analyze the influence of health on the poverty level in Sibolga City and its relationship with the poverty level because life expectancy in Sibolga City is still relatively low. Data collection techniques used questionnaires with a sample size of 40 respondents, structured and unstructured interviews and observations on research objects with the variables Life Expectancy (X1), Health (X2), Poverty (Y1), and Education (Z). . The data analysis techniques used are simple regression analysis, hypothesis testing (t test and f test), coefficient of determination test and path analysis test. Based on the results of Fcount (163.572) > F table (3.25) it can be concluded that the hypothesis states that the variables Life Expectancy (X1), Health (X2) and Education (Z) have a joint (simultaneous) and significant effect on Poverty (Y) accepted. The results of the research show that life expectancy and health have an influence on poverty levels with education as an intervening approach in society. However, the health variable has no influence on education as an intervening variable in this study. So the researchers concluded that based on the data analysis carried out by the researchers there was a direct positive and significant influence on life expectancy, health and education on poverty in Sibolga. With an influence level of 57.9%.Keywords: Life Expectancy, Health, Education and Poverty